Barriers and motivation for presumptive tuberculosis case referral: qualitative analysis among operators of community medicine outlets in Ghana - M.P Kwabla; C. J. Klett-Tammen; S. Castell (BMC, 2022)
Abstract Background Community medicine outlets (CMOs) are the first point of call for individuals presenting with cough in Ghana. Although operators of CMOs comprising pharmacists and over-the-counter (OTC) medicine sellers largely support the public-private mix strategy which seeks to engage pharmacies in tuberculosis (TB) case detection, a significant proportion is not involved in TB referral services. The study explores the barriers to and motivation for presumptive TB case referral among CMO operators. Methods We used open- and close-ended questions nested in a telephone survey which assessed factors associated with presumptive TB case referral among CMO operators (n = 465). We interviewed participants using computer assisted telephone interviews and analysed the qualitative data using adjusted Mayring's structured qualitative content analysis. Results Based on participants' own experiences, non-referral was attributed to negative attitudes of presumed cases (48.2%) and inability to meet the financial demands of referred presumed cases (26.3%). Regarding their perception of barriers to TB referral for their professional colleagues, an assumed lack of TB training (44.5%) and an assumed negative attitude of operators (43.6%) were mentioned. From close-ended questions, most chosen barriers to referral were: the assumption of not having seen a presumptive TB case yet (31.8%), lack of TB training (22.2%) and no monetary motivation for operators (10.5%). Most operators (81.6%) view TB referral services as their social responsibility and feel self-motivated to refer cases in order to control the spread of TB in their communities. Of 152 further comments extracted as recommendations to improve referral, 101 (66.4%) of respondents would only refer with the availability of support systems in the form of TB training and making TB diagnostic testing more accessible. Conclusion Operators of CMOs are predominantly self-motivated to refer presumptive TB cases. Barriers to referral might be mitigated by providing more training to operators and specific financial support such as reimbursement of travel costs to presumptive cases.